Towards a Transformative Pedagogy for Peace in Venezuela: An Analysis of the Gap between Curricular Intent and Teaching Practice: Towards a Transformative Pedagogy for Peace in Venezuela: An Analysis of the Gap between Curricular Intent and Teaching Practice - Reyes, Teresa (Opción, 2025)
This report analyzes the disjunction between curricular intention and pedagogical praxis in peace education in Venezuela. Through the analysis of teacher discourse, a gap that leads to a positivist-technical pacifist model is evidenced, which is far from the sociocritical vision of the curriculum. It is concluded that the didactic weaknesses of the teacher lead them to adopt control and repression strategies, perpetuating a cycle of unresolved violence. A set of guidelines is proposed to catalyze the transition towards a transformative pedagogy, anchored in humanism and critical theory.